Patient health portal: a calendar paradigm - Figueiredo, J. P.; Costa, C. J.; Aparicio, M. (Workshop on Open Source and Design of Communication, OSDOC 2012, 2012)
In this paper, we propose a conceptual model of a patient health portal based on a calendar paradigm. The study begins with a literature review on health portals and their stakeholders. Then, to support the proposed concept, we made an analysis of the state of the art in health portals and their main features. We propose a conceptual model for a user centered health portal and its needs. We also make an implementation of the conceptual model in an open source content management system (Drupal). Our study does also include the preliminary results of a survey to a group of key users.